A COMPARATIVE STUDY ON CUSTOMER SATISFACTION TOWARDS PERFORMANCE OF NOBLE HONDA BIKES (International Journal of Food and Nutritional Sciences, 2022)
The Automobile company gain market leadership only if understands the consumer taste and preference for final solution that delights consumer through superior value, quality and service, consumer preference is a vital factor in marketing. Consumer preference and customer satisfaction are similar, attributed in broad prospective. In order to accomplish this objective a market survey was conducted with 125 respondents in the study are. Advertisement campaign should aim at reaching the ultimate custom and the authorized dealers should also device a suitable advertisement to catch local customers. The introductions of Honda bikes have revolutionaries in the field of two wheeler industry. Large number of fancy two wheeler should be introduced by the company. A survey is done among the customers of Honda to study of the brand after the split. Customer opinions are recorded about their choice of the brand .It is concluded from the study that the Honda motor company gaining market share in two wheeler industry and what happen after split the Honda